Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 211727 by Spillover last updated on 18/Sep/24

Answered by MrGaster last updated on 03/Nov/24

=∫_(−(π/4)) ^(π/4) (((π−4x)tan x(1+tan x))/(1−tan^2 x))dx  =∫_(−(π/4)) ^(π/4) (((π−4x)tan x+(π−4x)tan^2 x)/(cos^2 x))dx  =∫_(−(π/4)) ^(π/4) (π−4x)tan x sec^2 xdx+∫_(−(π/4)) ^(π/4) (π−4x)tan^2 x sec^2 xdx  =∫_(−(π/4)) ^(π/4) (π−4x)tan xd(tan x)+∫_(−(π/4)) ^(π/4) (π−4x)tan^2 xd(tan x)  =[(((π−4x)tan^2 x)/2)]_(−(π/4)) ^(π/4) −∫_(−((π )/4)) ^(π/4) (−4)((tan^2 x)/2)dx+[(((π−4x)tan^3 x)/3)]_(−(π/4)) ^(π/4) −∫_(−(π/4)) ^(π/4) (−4)((tan^3 x)/3)dx  =[((π tan^2 x)/2)−2 tan^2 x]_(−(π/4)) ^(π/4) +[((π tan^3 x)/3)−((4 tan^3 x)/3)]_(−(π/4)) ^(π/4)   =[(π/2)−2]tan^2 (π/4)−[(π/2)−2]tan^2 −(π/4)+[(π/3)−(4/3)]tan^3 (π/4)−[(π/3)−(4/3)]tan^3 −(π/4)  =[(π/2)−2]−[(π/2)−2]+[(π/3)−(4/3)]−[(π/3)−(4/3)]  =0+0  =0

=π4π4(π4x)tanx(1+tanx)1tan2xdx=π4π4(π4x)tanx+(π4x)tan2xcos2xdx=π4π4(π4x)tanxsec2xdx+π4π4(π4x)tan2xsec2xdx=π4π4(π4x)tanxd(tanx)+π4π4(π4x)tan2xd(tanx)=[(π4x)tan2x2]π4π4π4π4(4)tan2x2dx+[(π4x)tan3x3]π4π4π4π4(4)tan3x3dx=[πtan2x22tan2x]π4π4+[πtan3x34tan3x3]π4π4=[π22]tan2π4[π22]tan2π4+[π343]tan3π4[π343]tan3π4=[π22][π22]+[π343][π343]=0+0=0

Commented by Spillover last updated on 03/Nov/24

great.thank you

great.thankyou

Terms of Service

Privacy Policy

Contact: info@tinkutara.com